Computational and experimental study of heat transfer in rotating ribbed radial turbine cooling passages - Pearce, R; Ireland, P; He, L; McGilvray, M; Romero, E (American Society of Mechanical Engineers, 2015)
This study investigates the effect of rotation on the Nusselt number distribution within ribbed radial turbine cooling passages representative of systems used in current jet engines. The results are unusual in that the cooling passage length to diameter ratio is engine representative and full distributions of local Nusselt number have been measured using the transient liquid crystal method. The results are compared to RANS CFD simulations and the level of agreement discussed in detail. A triple-pass serpentine passage is investigated, which includes 45° filleted rib-turbulators and 180° curved bends. The first two passes have an aspect ratio of 1:4 which are radially inward and outward respectively, with the final pass being radially outward with an aspect ratio of 1:2. The Reynolds, Rotation and Buoyancy numbers are all representative of a passage within a HP turbine blade of a gas turbine engine at 97000/108000, 0.081/0.088 and 0.052/0.035 respectively for the 1:4/1:2 aspect ratio passages. CFD simulations are found to give good predictions under stationary conditions however significant differences are observed when rotation is introduced. The Nusselt number distributions depend strongly on both rotation and upstream flow conditions created by the specific geometry.